Location-Aware Real Time Oceanographic Model to Prevent Coastal Drowning - Pradeep, H.B.A.C.; Nandana, R.G.; Thirimawithana, R.; Meegama, R.G.N. (International Conference on Emerging Trends in Engineering, Technology and Science, Hyderabad, India, 2015, 2015)
Attached

A majority of Asian countries are mainly agricultural economies with abundant water resources including coastal regions. Drowning is the second leading cause of accidental deaths in the world, next to road accidents. In Sri Lanka, approximately 1050 people die annually from drowning. This paper provides a novel approach to identify sea level behavior and predict a safe level of sea depth to swim and bath in coastal areas using a dynamically adjustable linear equation that focuses on several related facts affecting the safety of swimmers. A centralized server based system gathers relevant facts and Builds a data storage containing above mentioned facts. A user can directly execute a mobile based application to identify a safety grid around his bathing area using updated weather information. The proposed system will gather relevant environmental data using bathymetric maps, satellite images and online weather stations about the target location. After collecting all relevant data, an oceanographic mathematical model is used to derive the probability of risk for bathing inside the target area. The system will then display a safe region in a grid on the mobile screen to user
Keywords: linear equation; diving; oceanographic data; drowning